ORAL-SYRGICAL TREATMENT OF PERIODONTAL POCKET WITH GUIDED BONE AND SOFT TISSUE REGENERATION - Evrosimovska, Biljana; Pop Janeva, Ivana; PopJaneva, Bojana; Nikolovski, Bruno (Journal of Morphological Sciences, 2022)
Periodontal disease is defined as a complex, multifactorial disease characterized by the loss of connective tissue attachment with destruction of periodontal tissues. The aim of periodontal therapy is to eliminate inflammatory process, prevent the progression of periodontal disease and also to regenerate the lost of periodontal tissues. Loss of the bone support by creating a periodontal pocket is one of the most common cause of tooth extraction. Their treatment can be conservative and surgical. The purpose of this paper is to demonstrate the treatment of infrabony  periodontal defects  with bone and soft tissue regeneration. On periodontal examination and radiographic evaluation, the female 56-year-old patient presented with an infrabony defect extending up to apical third of the mesial side of the right maxillary second molar with a probing depth of 8 mm. After conservative periodontal treatment, oral surgical intervention was performed including open flap debridement and filling the defect with xenograft and plasma rich fibrin. The application of xenograft and Plasma rich fibrin resulted in bone regeneration of the defect and successful fixed prosthodontic solution. Guided bone and soft tissue regeneration using xenograft and fibrin-rich plasma gives successful radiological and clinical signs of bone augmentation and consolidation of defects caused by loss of tooth attachment. Keywords: periodontal pocket, xenograft, PRF. https://doi.org/10.55302/JMS2251179e